The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pcbi.1006616
|View full text |Cite
|
Sign up to set email alerts
|

SFPEL-LPI: Sequence-based feature projection ensemble learning for predicting LncRNA-protein interactions

Abstract: LncRNA-protein interactions play important roles in post-transcriptional gene regulation, poly-adenylation, splicing and translation. Identification of lncRNA-protein interactions helps to understand lncRNA-related activities. Existing computational methods utilize multiple lncRNA features or multiple protein features to predict lncRNA-protein interactions, but features are not available for all lncRNAs or proteins; most of existing methods are not capable of predicting interacting proteins (or lncRNAs) for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 75 publications
0
90
0
1
Order By: Relevance
“…RWNS fused different biological information related to small molecules and miRNAs. However, it may be improved by integrating more data, for example, functional associations between microRNAs and long non-coding RNAs (Zhang et al, 2018b). More importantly, how to integrate these data is still an ongoing challenge.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…RWNS fused different biological information related to small molecules and miRNAs. However, it may be improved by integrating more data, for example, functional associations between microRNAs and long non-coding RNAs (Zhang et al, 2018b). More importantly, how to integrate these data is still an ongoing challenge.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Recently, one broad theme is that lncRNAs can drive the assembly of RNA-protein complexes by facilitating the regulation of gene expression (Rinn and Chang, 2012;Chen and Yan, 2013;Hentze et al, 2018;Munschauer et al, 2018;Nozawa and Gilbert, 2019). lncRNAs achieve their specific functions by interacting with multiple proteins and thus regulating multiple cellular processes (Zhang et al, 2018c;Pyfrom et al, 2019). Studies reported that lncRNAs can activate post-transcriptional gene regulation, splicing, and translation by binding to proteins (Zhang et al,.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs achieve their specific functions by interacting with multiple proteins and thus regulating multiple cellular processes (Zhang et al, 2018c;Pyfrom et al, 2019). Studies reported that lncRNAs can activate post-transcriptional gene regulation, splicing, and translation by binding to proteins (Zhang et al,. 2018c;Li et al, 2019a) Therefore, identifying possible lncRNA-protein interactions (LPIs) is essential for unraveling lncRNA-related activities (Qian et al, 2018;Zhang et al, 2018c;Zhao et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a powerful complementary tool for biological and clinical experiments, many computational approaches have been developed to effectively predict the lncRNA-disease associations (Zou et al, 2016;Chen et al, 2017;Zhang et al, 2018c;Gong et al, 2019;Yue et al, 2019). Under the assumption that similar diseases are more likely to be associated with functionally similar lncRNAs, Chen et al proposed Laplacian regularized least squares for lncRNA-disease association in terms of a semi-supervised learning framework (Chen and Yan, 2013).…”
Section: Introductionmentioning
confidence: 99%